Diplomacia da inovação: o percurso singular do Itamaraty na internacionalização dos ecossistemas de inovação brasileiros e o papel do diplomata na linha de frente - Juliano Alves Pinto (2020)
This dissertation seeks to situate the concept of innovation diplomacy in the light of Brazilian foreign policy and the normative legislative framework on innovation, especially focused on the internationalization of both the Brazilian innovation ecosystems and the so-called Brazilian System of Innovation (SBI). Considering that innovation diplomacy has currently become part of the State policy of countries aspiring to power, two important contradictions are pointed out: 1) the non-formal attribution to Brazil’s Ministry of Foreign Affairs (MRE) of any role with regard to the internationalization of ecosystems of Brazilian innovation; and 2) the MRE's failure to consider that innovation deserves to be subject of foreign policy. The work has been able to verify, through the examination of primary sources (diplomatic cables) that, until 2017, the only possible standard for implementing diplomacy of innovation within the scope of the MRE was that of the diplomat acting proactively in the diplomatic posts they serve, based on the appropriation of the concept of street-level bureaucrat, enshrined in political science, in which the agent on the front line is both executor and formulator of public policy, and in the case of the MRE, of foreign policy. Concepts related to the notion of national interest and the importance of innovation to increase the competitiveness of countries are elucidated, which is why it is concluded that Brazil, unlike most of the aspiring countries, does not consider innovation as part of a national project, which is corroborated by the current practice of cutting public spending on scholarships and research. The comparison with public policies aimed at promoting exports, whose normative framework goes back to the sixties and assumes a central role for the MRE in conducting external actions, is useful to reinforce the contrast with the area of innovation, which is far from being considered priority when compared to the first, especially since the proper integration of the MRE with the SBI has not yet been formally accomplished.